Documentary Practice and Transnational Feminist Theory - White, Patricia (A Companion to Contemporary Documentary Film, 2015)
This paper looks at five documentaries on activism around ending the practice of female genital cutting (FGC) in Africa. All were made by or in partnership with UK and US producers and are distributed by the New York-based non-profit media arts organization Women Make Movies. By tracing changing political and representational strategies in feminist documentaries on the issue and the varying terms on which the films engage their subjects and address their viewers, the chapter aims to put the specificity of independent documentary formats, practices, and institutions in dialogue with feminist theoretical critiques of the wider discourse on women's human rights. The chapter looks at Kaplan and Grewal's critique of the neo-colonialism of Alice Walker and Pratibha Parmar's Warrior Marks, the observational strategies of Kim Longinotto's The Day I Will Never Forget, the diasporic dimensions of Mrs. Goundo's Daughter and Sarabah, and the visual rhetoric of human rights models in Equality Now's Africa Rising. The cultural field of documentary constitutes a public sphere in which activist and theoretical debate, contested reception, and continually renewed cultural production articulate the productively shifting terms of transnational feminism.
Section: 10 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/9781118884584.ch10
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des industries culturelles; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Identités diasporiques; _Nettoyé

Postcolonial Modernism: Art and Decolonization in Twentieth-Century Nigeria - Okeke-Agulu, Chika (Duke University Press, 2015)
Written by one of the foremost scholars of African art and featuring more than 125 color images, Postcolonial Modernism chronicles the emergence of artistic modernism in Nigeria in the heady years surrounding political independence in 1960.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Créateur.rice noir.e; 5-Identités diasporiques; _Nettoyé